Striden om dødehavsrullerne - Riis, Anita Holm (Religionsvidenskabeligt Tidsskrift, 2000)
<span style="font-size: 9pt; font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Shruti; mso-fareast-language: DA; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-GB">Traditionally, the concept of objectivity has been connected with the natural sciences rather than the cultural sciences. In recent years there has even been talk of an outright subjectivist tendency in cultural research. The present article takes issue with this prejudice. Here a concrete example from the field of cultural studies is analysed (the dispute concerning the Dead Sea Scrolls) with the intention of laying bare the underlying concept of objectivity. The example shows that research in this field presupposes a distinct concept of objectivity.